2022
DOI: 10.3390/mi13070992
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrode Structure on Performance of Laser Direct Writing Cu-PI Flexible Humidity Sensor

Abstract: Electrode structure is an essential factor affecting the performance of flexible humidity sensors. In this study, Cu and Cu2 + 1O electrodes were printed by the one-step method using laser direct writing technology to reduce the nano–CuO ink on flexible substrate PI and to be used for a humidity sensor. The resistance of the humidity sensors with nine various electrode structures was measured under the relative humidity (RH) of 16–78%. It was observed that all sensors showed good humidity sensing characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Mueller et al observed that this effect increases with increasing aspect ratio of the NPs [28]. In a majority of previous studies, spin coating was chosen as the coating method [8,[15][16][17][18][19]. However, due to the shear thinning behavior of the PC, the coating thickness decreases outward from the center of rotation, making it difficult to achieve uniform coating thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mueller et al observed that this effect increases with increasing aspect ratio of the NPs [28]. In a majority of previous studies, spin coating was chosen as the coating method [8,[15][16][17][18][19]. However, due to the shear thinning behavior of the PC, the coating thickness decreases outward from the center of rotation, making it difficult to achieve uniform coating thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ionic solutions based on copper salts [9][10][11] or complexes [12] and deep eutectic solvents [13,14], copper oxides in the form of nanoparticles (NPs) suspensions can also be used. This enables a maskless, vacuum-free, flexible and direct writing technology that can be used on a wide range of substrates, such as glass [8,[15][16][17] and polymers [18][19][20]. A wide range of applications have already been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The repeatability test with increasing RH proves the suitability of patients with IAD in clinical settings. Therefore, we validated 100 kHz as the operating frequency in the following testing, related to previous studies [ 1 , 4 , 5 , 31 , 34 ]. With a variation of 20–90% RH, the change in five-volt voltage exhibited a relatively small pore size of 0.1 This means that, if a mattress is subjected to a high humidity change, it can be inconvenient and the sensing material of the humidity sensor is not good for patients with IAD in clinical settings [ 1 , 2 , 4 , 8 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another common mechanism based on reduction principles is the use of metal oxide NPs as metallic precursors. This method has been adopted for several transition metals, using CuO x , [ 36,38,87,175–178 ] NiO x , [ 86,149,179 ] CoO x , [ 180 ] as well as NP mixtures. [ 181,182 ] This mechanism is based on mixing oxide NP precursors with similar reducing agents (e.g., PVP, [ 38,87 ] ethylene glycol), [ 36,182 ] while laser irradiation and resulting photothermal processes promote the removal of oxygen over the metal oxide NP structure.…”
Section: Mechanisms For Materials Synthesis and Conversion Through Dlwmentioning
confidence: 99%